THE INFLUENCE OF INDIVIDUAL AND JOB CHARACTERISTICS ON EMPLOYEE PERFORMANCE IN THE FORESTRY SERVICE OF WEST SUMATRA PROVINCE - Nigel Angela; Lucy Chairoel (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the effect of Individual and Job Characteristics both partially and simultaneously on employee performance at agencies in the Forestry Service of West Sumatra Province. This research is Quantitative research. The sample of this study amounted to 100 people. Sample determination was carried out by the Saturated Sampling method. Data collection using questionnaires and observations, while data analysis was carried out using multiple linear regression analysis. The results of the study at a significance level of 5% showed that: 1) The t test result on the Individual Characteristics variable is 2.808, with a significant value of 0.006 which means that Individual Characteristics have a positive and significant effect on employee performance. 2) The t test result on the Job Characteristics variable is 2.579, with a significance value of 0.011, which means that Job Characteristics have a positive and significant effect on employee performance. 3) The coefficient of determination (R2) test for variables X1, X2 is 0.536, which means that employee performance can be influenced by individual and job characteristics by 27.2%, while the remaining 72.8% is influenced by other factors that tid.